Intraindividual variability and epistemic (in)dependence of teacher during both expositive and guided-participative classes - Rosellí, Néstor D. (2011)
The objective of this research is to compare the epistemic development of two opposite teaching styles: expositive and guided-participative, in a natural setting. The aim was to analyse some non-explicit or hidden differential traits of each style and make them explicit. This analysis is focused on the instructive development of knowledge, that is, the teaching process itself and not the learning outcomes. These hidden differential traits concern the stability-variability of teaching and the dependence-independence of the teacher from the epistemic.source. Four biology teachers were invited to teach their own secondary students the same extracurricular subject. It was agreed that two of them would use an expositive style, while the two others implemented a participative style. Results show great differences between both teaching styles. Expositive style displays a more fixed intraindividual pattern in the epistemic development, while the participative teacher is more variable in the way he teaches the same knowledge. On the other hand, the participative style is more independent from the epistemic source (the scientific text offered to all teachers), while the expositive modality sticks more to the original source.